Empirical Study of Twin Deficits in Indonesia: The Relationship Between Causality and Early Warning System of Twin Deficits' Cause - Kuncahyo, Prawudya Dery (Journal of Developing Economies, 2016)
The aim of this research is to investigate the causality of deficit budget with the current account deficit (twin deficits) in Indonesia and to detect the decision indicators of twin deficit as an early warning system model of twin deficits' occurrence. The research applied a quantitative approach with granger causative data to find the significant relationship of twin deficits in Indonesia. At the early stage, it analyzes the detection of twin deficits by using quantitative phenomenological approach in a form of mathematic formula calculation via non-parametric model with EWS signal extraction. It used 1 derivation standard (DS) and 24 months signal windows to extract signal. Signal extraction is applied to monitor the evolution of economic indicators which has a systematic tendency of twin deficits in Indonesia. Microsoft Office Excel 2007 and E. Views 7 are the software used within this research. The result of this research signified that there is a relationship between twin deficits in Indonesia with the budget deficit which is influencing the current account deficit. It strengthens the Twin Deficits Hypothesis (TDH) that explains the existence of budget deficit will affect the current account deficit by access of interest rate. Additionally, the result of a signal extraction calculation from the chosen indicator variable trend showed a positive signal of twin deficits. It is justified by the abnormal behavior of variables which states up to 50 percent probability. Those variables are export growth, import growth, terms of trade, inflation, growing industrial sector, real exchange rate, foreign reserve growth, and growth of world oil price. Keywords: Budget deficit, Current Account Deficit, Early Warning System.JEL: F32, F41